ChemInform Abstract: Facile Synthesis of 4‐Aryl and Alkyl Substituted, N6‐Alkylated Pyridazine‐3, 6‐diamines. Issue 14 (March 2016) - Wlochal, Joanna; Bailey, Andrew
Abstract: N‐unprotected substrate (I) undergoes Suzuki or Negishi coupling to afford 4‐aryl and 4‐alkyl substituted pyridazines.